Perception Of Badminton Players Regarding Coaching Proficiency Of Male Directors Physical Education At College Level - Nisar Ahmed Khaskheli; Muhammad Hashim Darya; Muhammad Murad Pirzada; Arbab Ali Leghari; Farhan Ali Khaskheli; Akhtar Ali Khaskheli; Duae Maryam (Kurdish Studies, 2024)
The coaching skills include all coaching domains like technical, strategical, motivational, character building and the skills to compete in the tournaments. The investigation was ensured while selecting 200 Badminton players studying in colleges as a sample of the study using a convenience sampling technique. The players of Badminton assessed the coaching efficiency of Directors of Physical Education (DPEs) who also work as coaches, utilizing a scale of Coaching efficacy (survey questionnaire) introduced by Feltz, et al., 1999. The utilized scale contained all coaching domains. The collected data was analyzed using the (SPSS) 22 version. Frequencies, percentages, and means were computed to analyze data. The results depict that there is a close, significant and positive relationship between coaching with all the coaching domains that include, Players' motivation, players' game strategy skills, players' capability to compete in the tournaments, players' technical skills and players' character building. The present study recommends that the coaching camps and training programs should be planned and organized for the capacity development of DPEs as per their specialized fields/ games including Badminton and others so that the more effective and efficient coaching may be imparted to college level players of all games.